Effects of lifestyle intervention on long‐term risk of diabetes in women with prior gestational diabetes: A systematic review and meta‐analysis of randomized controlled trials. (5th August 2020) - Li, Ninghua; Yang, Yingzi; Cui, Dingyu; Li, Changping; Ma, Ronald C.W.; Li, Jing; Yang, Xilin
Summary: We performed two meta‐analyses to estimate the effects of lifestyle intervention during pregnancy and after delivery on the risk of postpartum diabetes among women with gestational diabetes mellitus (GDM). We searched the major databases to retrieve articles published in English or Chinese before 15 December 2019. The inclusion criteria were randomized controlled trials (RCTs) of diet, physical activity or both, conducted during or after pregnancy among women with GDM. The exclusion criteria were (1) having type 1 or type 2 diabetes before the intervention and (2) without postpartum diabetes documented. Fixed‐effects model analysis was used to obtain the pooled relative risks (RRs) and 95% confidence intervals (CIs) of lifestyle intervention for diabetes in women with GDM. Four RCTs were identified to have implemented the intervention during pregnancy ( n = 2883) and 10 to have conducted it within 3 years after delivery ( n = 1733). Lifestyle intervention during pregnancy was not effective at reducing the risk of postpartum diabetes (RR: 0.91, 95%CI: 0.66–1.25). However, lifestyle intervention initiated within 3 years after delivery was highly effective in reducing the risk of postpartum diabetes (pooled RR: 0.57, 95% CI: 0.42–0.78). In conclusion, our findings support the early initiation of lifestyle intervention in women with GDM for the prevention of diabetes.